2010
DOI: 10.1111/j.1551-2916.2010.04153.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hafnia Powder Prepared from an Oxychloride Sol–Gel

Abstract: Hafnium‐containing compounds are of great importance to the semiconductor industry as a high‐κ gate dielectric to replace silicon oxynitrides. Here, the crystallization processes and chemistry of bulk hafnia powders are investigated, which will aid in interpretation of reactions and crystallization events occurring in thin films used as gate dielectrics. Amorphous hafnia powder was prepared via a sol–gel route using the precursor HfOCl2·H2O. The powders were subjected to various heat treatments and analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…In our previous study, looking at HfO 2 prepared from hafnium oxychloride precursor, it was found that the HfO 2 precursor crystallized into m ‐HfO 2 as expected upon heating. However, after heating in vacuum or in an inert environment, a different crystallization route was taken where tetragonal HfO 2 ( t ‐HfO 2 ) formed simultaneously with m ‐HfO 2 at temperatures below 1000°C, before transforming into m ‐HfO 2 as the crystallite size increased.…”
Section: Introductionmentioning
confidence: 60%
See 4 more Smart Citations
“…In our previous study, looking at HfO 2 prepared from hafnium oxychloride precursor, it was found that the HfO 2 precursor crystallized into m ‐HfO 2 as expected upon heating. However, after heating in vacuum or in an inert environment, a different crystallization route was taken where tetragonal HfO 2 ( t ‐HfO 2 ) formed simultaneously with m ‐HfO 2 at temperatures below 1000°C, before transforming into m ‐HfO 2 as the crystallite size increased.…”
Section: Introductionmentioning
confidence: 60%
“…This difference in hydration state resulted in slight changes to the crystallization temperatures obtained for different phases observed when heating sample prepared from the two precursors. For this reason and for consistency and comparison with previous study, all the samples used in this study have been prepared with the Fluorochem precursor.…”
Section: Methodsmentioning
confidence: 96%
See 3 more Smart Citations